2016
DOI: 10.1002/ece3.2277
|View full text |Cite|
|
Sign up to set email alerts
|

Sex determination, longevity, and the birth and death of reptilian species

Abstract: Vertebrate sex‐determining mechanisms (SDMs) are triggered by the genotype (GSD), by temperature (TSD), or occasionally, by both. The causes and consequences of SDM diversity remain enigmatic. Theory predicts SDM effects on species diversification, and life‐span effects on SDM evolutionary turnover. Yet, evidence is conflicting in clades with labile SDMs, such as reptiles. Here, we investigate whether SDM is associated with diversification in turtles and lizards, and whether alterative factors, such as lifespa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
66
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 74 publications
(169 reference statements)
5
66
0
Order By: Relevance
“…Consistent with the hypothesis that species with ESD might have unequal sex ratios and therefore be prone to invasions by GSD to restore balanced sex ratios (Fisher, ), we find that transitions from ESD to GSD occur at higher rates than the reverse in both fish and squamates. Our results are also consistent with previous studies in squamates, which have also found that transitions from ESD to GSD are more common than the reverse (Gamble et al., ; Pokorná & Kratochvíl, ; Sabath, Itescu, et al., ). However, there is no difference in transition rates between ESD and GSD in turtles, possibly due to the longer lifespan of turtles (Sabath, Itescu, et al., ).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Consistent with the hypothesis that species with ESD might have unequal sex ratios and therefore be prone to invasions by GSD to restore balanced sex ratios (Fisher, ), we find that transitions from ESD to GSD occur at higher rates than the reverse in both fish and squamates. Our results are also consistent with previous studies in squamates, which have also found that transitions from ESD to GSD are more common than the reverse (Gamble et al., ; Pokorná & Kratochvíl, ; Sabath, Itescu, et al., ). However, there is no difference in transition rates between ESD and GSD in turtles, possibly due to the longer lifespan of turtles (Sabath, Itescu, et al., ).…”
Section: Discussionsupporting
confidence: 93%
“…However, these results were equivocal as net diversification intervals in birds, which have heteromorphic sex chromosomes, are similar to those in turtles and crocodylians (Philips & Edmands, ). Indeed, other analyses have found no association between diversification rates and the presence of ESD or GSD in turtles, squamates or birds (Organ & Janes, ; Sabath, Itescu, et al., ). Thus, there is not strong evidence that the presence of heteromorphic sex chromosomes influences speciation rates in vertebrates.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Most turtles exhibit the ancestral TSD from which GSD evolved independently multiple times, sometimes as male-heterogametic (XX/XY) and other times as femaleheterogametic (ZZ/ZW) sex chromosome systems [Valenzuela and Adams, 2011;Bachtrog et al, 2014;Sabath et al, 2016]. Phylogenetic analyses vary in their estimate of the number of evolutionary transitions among sex-determining modes that are reconstructed in turtles [Valenzuela and Adams, 2011;Sabath et al, 2016].…”
mentioning
confidence: 99%
“…Phylogenetic analyses vary in their estimate of the number of evolutionary transitions among sex-determining modes that are reconstructed in turtles [Valenzuela and Adams, 2011;Sabath et al, 2016]. Recent molecular evidence supports the scenario that 5 transitions from TSD to GSD and 2 reversals back to TSD from GSD occurred during turtle evolution [Valenzuela and Adams, 2011].…”
mentioning
confidence: 99%